(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
he court decision in favor of the Diario de Yucatán is one of the most important cases concerning freedom of the press in the irst half of twentiethcentury Mexico. Although the paper might have been shuttered for its conservative tone, publishing articles against the revolutionary government of Bartolomé García Correa, who was close to ex-president Plutarco Elías Calles and the Partido Nacional Revolucionario (pnr), it received legal approval to keep printing. he judicial process of Diario de Yucatán demonstrates increasing strength of the judicial system and the diferences at several levels of justice as Mexico recovered from war.